A prospective observational study of thyroid dysfunctions during pregnancy in a tertiary care hospital - Chunchaiah, Sarojamma; Prasad, Nagendra; B. M., Murali; B. M., Rupakala; Rangaiah, Nagarathnamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Thyroid dysfunctions are the second most common endocrine disorders seen during pregnancy. Overt or subclinical thyroid dysfunction during pregnancy adversely affects maternal and fetal outcomes. Maternal euthyroid status in early gestation period and optimal transfer of thyroxine to fetus is crucial for the optimal growth, development and maturation of fetal nervous system. This study is undertaken to know the magnitude of thyroid dysfunctions during pregnancy in our region and to validate the need for early detection of maternal thyroid dysfunctions by antenatal screening. Methods: It was a hospital based prospective study over a period of one year. According to our study criteria, blood samples were collected from consenting pregnant woman during their first antenatal visit and analyzed for TSH level by ultrasensitive method. Free T3 and Free T4 were assayed in patients showing abnormal TSH level and anti thyroid peroxide antibodies tested in all hypothyroid patients. All pregnant woman enrolled were followed up throughout the pregnancy, labour and postpartum to note any maternal and fetal adverse outcomes. The data obtained were analyzed and pregnancy outcomes compared between women showing thyroid dysfunctions and euthyroid state. Results: Among 800 pregnant women studied 88.75% were euthyroid and 11.25% showed thyroid dysfunction, affecting more in the age group 21-25 years and multigravidae. Prevalence of hypothyroidism was 10.12%, presenting as subclinical hypothyroidism (7.37%) and overt hypothyroidism (2.75%). Hyperthyroidism was seen in 1.12% of cases, 0.87% of them presented subclinically and 0.25% overtly. Risk factor was present in 29.62% of hypothyroid group and 33.33% of hyperthyroid group. Pregnancy complications were seen in 55.55% of thyroid dysfunctional group, preeclampsia being the most common complication. Conclusions: Our study showed 11.25% prevalence of thyroid dysfunction in pregnant women and commonest dysfunction was hypothyroidism in subclinical form. Adverse pregnancy outcomes were seen in 55.55% woman having thyroid dysfunctions. Absence of risk factor was noted in upto 70% of the cases with thyroid dysfunctions hence the diagnosis will be missed if only high risk cases are screened. Therefore universal screening is recommended early in pregnancy to identify and correct thyroid dysfunctions to prevent the associated adverse pregnancy outcomes.